Answer:
Step-by-step explanation:
Answer:D
Step-by-step explanation:
(3x^3 - 5x^2 + 4x - 9)-(7x^3 - 8x^2 - 5x + 10)
open brackets
3x^3 - 5x^2 + 4x - 9 - 7x^3 + 8x^2 +5x - 10
Collect like terms
3x^3-7x^3-5x^2+8x^2+4x+5x-9-10
-4x^3+3x^2+9x-19
Answer:
x = 1
Step-by-step explanation:
We need to solve for x by isolating the variable.
First, expand the parentheses:
2(x + 1) = 4
2 * x + 2 * 1 = 4
2x + 2 = 4
Then subtract by 2:
2x + 2 - 2 = 4 - 2
2x = 2
Finally, divide by 2:
2x/2 = 2/2
x = 1
Thus, x = 1.
Hope this helps!
They’re all -4 ,, what exactly are you asking ?
Answer:
1. True, 2. False, 3. I am blind.
Step-by-step explanation:
For the 3rd one I cannot confirm becaue I am blind.